Ginsenoside Rb1 Attenuates Triptolide-Induced Cytotoxicity in HL-7702 Cells via the Activation of Keap1/Nrf2/ARE Pathway - Peng, Hulinyue; You, Longtai; Yang, Chunjing; Wang, Kaixin; Liu, Manting; Yin, Dongge; Xu, Yuchen; Dong, Xiaoxv; Yin, Xingbin; Ni, Jian (Frontiers in Pharmacology, 2022)
Triptolide (TP) is the major bioactive compound extracted from Tripterygium wilfordii Hook F. It exerts anti-inflammatory, antirheumatic, antineoplastic, and neuroprotective effects. However, the severe hepatotoxicity induced by TP limits its clinical application. Ginsenoside Rb1 has been reported to possess potential hepatoprotective effects, but its mechanism has not been fully investigated. This study was aimed at investigating the effect of ginsenoside Rb1 against TP-induced cytotoxicity in HL-7702 cells, as well as the underlying mechanism. The results revealed that ginsenoside Rb1 effectively reversed TP-induced cytotoxicity in HL-7702 cells. Apoptosis induced by TP was suppressed by ginsenoside Rb1 via inhibition of death receptor-mediated apoptotic pathway and mitochondrial-dependent apoptotic pathway. Pretreatment with ginsenoside Rb1 significantly reduced Bax/Bcl-2 ratio and down-regulated the expression of Fas, cleaved poly ADP-ribose polymerase (PARP), cleaved caspase-3, and -9. Furthermore, ginsenoside Rb1 reversed TP-induced cell cycle arrest in HL-7702 cells at S and G2/M phase, via upregulation of the expressions of cyclin-dependent kinase 2 (CDK2), cyclin E, cyclin A, and downregulation of the expressions of p53, p21, and p-p53. Ginsenoside Rb1 increased glutathione (GSH) and superoxide dismutase (SOD) levels, but decreased the reactive oxygen species (ROS) and malondialdehyde (MDA) levels. Pretreatment with ginsenoside Rb1 enhanced the expression levels of nuclear factor-erythroid 2-related factor 2 (Nrf2), total Nrf2, NAD(P)H: quinone oxidoreductases-1 (NQO-1), heme oxygenase-1 (HO-1), and Kelch-like ECH-associated protein 1 (Keap1)/Nrf2 complex. Therefore, ginsenoside Rb1 effectively alleviates TP-induced cytotoxicity in HL-7702 cells through activation of the Keap1/Nrf2/ARE antioxidant pathway.